NGHIÊN CỨU THÀNH PHẦN HÓA HỌC CỦA CÂY MỘC KÝ NGŨ HÙNG DENDROPHTOE PENTANDRA (L.) MIQ., HỌ CHÙM GỬI (LORANTHACEAE) KÝ SINH TRÊN CÂY MÍT ARTOCARPUS INTEGRIFOLIA VÀ CÂY NA ANNONA SQUAMOSA - Hạt, Nguyễn Hoàng; Hào, Nguyễn Công; Khoa, Nguyễn Cửu (Vietnam Journal of Chemistry, 2012)
Six compounds, b-sitosterol (1),  daucosterol (2),  3-friedelanol (3), glyxerol-1,2-dihexadecanoat-3-O-β-D-glucopyranose (4), heptacosanoic acid (5) and hesperidin (6), were isolated from leaves and stems of Dendrophtoe pentandra, which is a parasitic plant on Artocapus integrifolia and Annona squamosa in Vietnam. Their structures were determined by means of  ESI-MS and NMR spectroscopic.